Homogeneous poly (L-lactic acid)/chitosan blended films - Ferreira, C. S. (2014)
This work reports an optimized and simple methodology for the preparation of poly(L-lactic) acid/chitosan (CHT) blends by solvent casting based on the use of a common solvent: hexafluor-2-propanol. Films with different component fractions were successfully prepared and did not show visible phase separation. Such biodegradable films have potential to be used in distinct biomedical and environmental applications. The composition effect on film wettability and morphology was investigated by contact angle measurements and scanning electron microscopy. Swelling measurements were also conducted. The composition effect on their thermal properties was analyzed by differential scanning calorimetry. It was found that crystallization is almost suppressed for CHT fractions above 50%. The film miscibility as a function of their composition was evaluated by optical microscopy and Fourier transform infrared spectroscopy imaging. These results evidenced the good miscibility at the microscopic level of the blends. The viscoelastic behavior of the developed films was also studied for the first time by dynamical mechanical analysis (DMA) in an unconventional way: their mechanical properties were measured while they were immersed in gradient compositions of water/ethanol mixtures. This allowed to analyze the glass transition dynamics of the CHT fraction, which would not be possible with conventional DMA tests. DMA temperature scans were also conducted.